Intelligent Electric Vehicle Charging Controller - Cardoso, Filipe (2021)
For domestic consumers, electricity tariffs usually have two components: one is related to the maximum available current/total power (billed in C/day) and the other concerns to the energy consumption (C/kWh). The main switchboard current is usually limited, according to the contracted power level, by way of automatic switches. To avoid main switchboard tripping by current limit violation, Electric Vehicle (EV) owners may decide to increase their contracted power (and the energy bill) or to adopt charging strategies that limit the global consumption (EV plus house needs) to the contracted current/power. In this paper, an Intelligent Electric Vehicle Charging Controller (IEVCC), allowing to use the contracted power to the maximum extent, is presented. A set of user configurable parameters can be used to define the controller behavior, in order to prevent a full switch-off. Two versions are described: a single user version that can be used at private houses and a mesh version that can be used in multi apartment buildings, providing information about consumed energy, time of use, costs and past bills.